The Analysis of Students English Pronounciation In Term Of Stress Errors At Smp It Darul Ulum Pao Etang - Riskiyanti, Riskiyanti A; Maming, Khadijah; Sianna, Sianna (La Parole : Journal of Language Teaching and Pedagogy, 2023)
The purpose of the research is to describe out the students’ English pronunciation in term of stress errors at SMP IT Darul Ulum Pao Etang. The researcher used descriptive qualitative research method. The researcher analyzed the stress error in reading aloud. In this research, the researcher finds out the result of the research using descriptive qualitative research. It will describe the students’ pronunciation in term of stress and errors. The population of this research is the eighth grade of SMP IT Darul Ulum Pao Etang which consisting of one class, which consisted of 18 students and will be divided into one class. The subject of this researcher is the eighth grade of SMP IT Darul Ulum Pao Etang Academic years 2020/ 2021. The subject of the research is part of a population of individual information is obtain. The aimed of the research it can be concluded that students at SMP IT Darul Ulum Pao Etang did some mistake in pronounce the words which included 2, 3, 4 dan 5 syllable. Besides that, the researcher found several caused of stress errors based on the students learning experience suh as unfamiliar word, homograph, lack of practice, mother tounge case and etc.